SCENARIO FORECASTING REVENUE MANAGEMENT STRATEGY FOR UKRAINIAN HOTELS - Margaryta Boiko; Myroslava Bosovska; Mariia Kulyk; Nadiia Vedmid (Agora International Journal of Economical Sciences)
An organizational mechanism for revenue management implementing is proposed: monitoring and analytics of metrics for efficient adaptation; dynamic pricing and market segmentation; partnerships and staff motivation. Pessimistic, realistic, and optimistic scenarios have been developed to ensure the long-term effectiveness of revenue management. The pessimistic scenario as a preventive indicator of a crisis situation is proposed to prevent cost dissipation in the face of rate changes, ensuring the preservation of resource potential and maintaining consumer interest in the hotel product. The realistic scenario which reflects situationally possible deviations in revenue dynamics and likely fluctuations in demand focuses on strategizing preventive marketing measures to influence demand depending on external conditions and resource potential. The optimistic scenario, representing a favorable forecast involves the use of a portfolio of strategies, the variability of which provides conditions for maximizing income and helps to determine the priority areas of investment in the revenue management subsystems.